2016 IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference (EIConRusNW) 2016
DOI: 10.1109/eiconrusnw.2016.7448133
|View full text |Cite
|
Sign up to set email alerts
|

The examination of the effects of quercus aegilops extract used as natural mordant on colourfulness features of natural dyeing

Abstract: Ecological textiles or eco textiles means a recyclable product or a product that can be recycled into an environmentally harmless product which has been produced by paying regard to environment during all process steps from, which does not harm the user. Natural dyeing, which is of great importance in the textiles industry in terms of being economical and applicable, has a number of advantages thanks to its features such as health, ecological cycle and providing biological availability. With the use of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…In a study, the usability of natural dye extracts obtained from Helichrysum arenarium and natural mordant obtained from Quercus aegilops in dyeing Karabük Eflani cloth, a local weave, was examined. It is reported that all the dyeings were red-nuanced in terms of lightness and darkness, and also in terms of yellowness and blueness, blue nuance was higher in the sample at 5% concentration, and yellow nuance was higher in other samples (Akkaya and Eyupoglu 2016). While investigating the dyeing of wool yarn with Adhatoda vasica extract as a natural dye, natural tannin extracts (gallnut (Quercus infectoria), pomegranate (Punica granatum) bark, and babool bark (A. nilotica)) were evaluated comparatively.…”
Section: Oak (Quercus)mentioning
confidence: 96%
“…In a study, the usability of natural dye extracts obtained from Helichrysum arenarium and natural mordant obtained from Quercus aegilops in dyeing Karabük Eflani cloth, a local weave, was examined. It is reported that all the dyeings were red-nuanced in terms of lightness and darkness, and also in terms of yellowness and blueness, blue nuance was higher in the sample at 5% concentration, and yellow nuance was higher in other samples (Akkaya and Eyupoglu 2016). While investigating the dyeing of wool yarn with Adhatoda vasica extract as a natural dye, natural tannin extracts (gallnut (Quercus infectoria), pomegranate (Punica granatum) bark, and babool bark (A. nilotica)) were evaluated comparatively.…”
Section: Oak (Quercus)mentioning
confidence: 96%
“…al., 2020;Özomay, 2009). Color strength values (K / S) of the printed samples were calculated according to Formula 7 using Kubelka-Munk equation (Özomay & Akalın, 2020;Akkaya & Eyupoglu, 2016).…”
Section: Color Measurementmentioning
confidence: 99%
“…The transfer printing material, for which a sublimation film layer is formed, has been conditioned in the printing room at a temperature range of 20-250 0 C and a relative humidity of 40-60% for 24 hours before printing (Akkaya & Eyupoglu, 2016). The main print films obtained were transferred on polyester and nylon textile fabrics using HP3803 flat thermal transfer printing machine at 150 0 C, 200 0 C with 30, 60 and 120 seconds transfer waiting time.…”
Section: Sublimation Transfer Printing Processmentioning
confidence: 99%
“…Recently, researchers have focused on investigating the natural dyeing of textile materials and their dyeability. Research has been conducted in the literature on "dyeing silk using Dwarf Elder fruit dye and Alkannin dye from Alkanna tinctoria" (Dayioglu et al, 2015;Adeel et al, 2022), "dyeing wool using Chamaecyparis Lawsoniana cone extract and madder and resedaluteola" (Kilinc et al, 2015;Hosseinnezhad et al, 2022), "dyeing of banana fibers with natural dye extracted from the turmeric plant" (Canbolat et al, 2015),"dyeing of cotton with Helichrysum Arenarium extract and a natural dye extracted from Syzygium cumini fruits" (Akkaya & Eyupoglu, 2016;Periyasamy, 2022), "dyeing of mohair fibers with natural dye extracted from Candelariella reflexa" (Eyupoglu et al, 2022), "dyeing of organic cotton fabrics with gardenia yellow from Gardeniae fructus seeds" (Jiang et al, 2022), "dyeing hemp with extract dye from stinging nettle" (Gürbüz, 2022). In this study, natural dyeing was carried out using sodium copper chlorophyll.…”
Section: Introductionmentioning
confidence: 99%